Grafos na educação básica: do formal ao lúdico - Silva, Luciano Pereira da (2020)
This work has the proposal to introduce graph theory in basic education, a subject of higher education mathematics that we can apply in elementary education in a playful way and, thus, take a contribution to the challenge teachers' diary, which is to motivate students to learn. We take a walk historical in the region where the beginning of graph theory studies is considered, as well as its advances and contributions of scholars over the years. We present the de nition and basic elements necessary for the understanding of the theory of graphs. We show Euler's solution to the most famous problem in the history of graph theory, the problem of the Seven Bridges of Königsberg. We solve others equally interesting problems. And nally, we propose activities that can be applied in basic education.